PENGEMBANGAN MODELPENDIDIKAN KARAKTER BERBASIS BUDAYA KERJA DI SEKOLAH MENENGAH KEJURUAN - Azwar Anas; Ngurah Ayu Nyoman Murniati; Endang Wuryandini (Pusat Studi Pendidikan dan Kreativitas Guru, 2021)
The purpose of this study is to design a work culture-based character education model in vocational high schools. This study uses a research and development design from Borg and Gall. Researchers use research and development at the first level where researchers conduct research to produce designs. The research begins with a preliminary study and needs analysis to design a work culture-based character education model through interviews and observations to SMK PGRI 1 Taman, SMK PGRI 3 Randudongkal and related industries. The research results found a factual model of character education which in its implementation has not been specifically adjusted to the value of work character. This model includes planning, organizing, implementing and supervising character education in Vocational High Schools. The findings in the field show that it is necessary to integrate between components in planning, organizing, implementing and supervising work culture-based character education in vocational high schools. The factual results were developed into a work culture-based character education model design in Vocational High Schools. The results of the model design are assessed and validated by educational experts and assessed by education practitioners through Focus Group Disscussion (FGD). The results of the assessment and validation by educational experts obtained a score of 54 out of the maximum score of 56, so a percentage of 96.43% was obtained, so if the value calculation and validation were classified based on the rating scale, qualitative criteria were obtained with the result